Biology concepts & connections - Campbell, Neil A. 1946-2004; Reece, Jane B.; Taylor, Martha R.; Simon, Eric J.; Dickey, Jean L. (Pearson/Benjamin Cummings, 2009)
This book continues to be the most accurate, current, and pedagogically effective non-majors text on the market. This extensive revision builds upon the book's best-selling success with exciting new and updated features. Key concept modules, seamlessly combining text and illustrations, help students keep the big picture in mind and pace their learning, while making it easy for professors to assign selected sections within a chapter. Also within the text, a variety of new chapter opening essays, Connection Modules, and new Evolution Connection Modules help students recognize and appreciate the connections between biology and the world they live in. BioFlix animations, available on the companion website and as part of the instructor resources, offer students unprecedented help in understanding important topics and help invigorate lectures, assignments, or online courses